Positive correlation of psoriasis vulgaris severity and HOMA-IR - Made Wardhana; Made Swastika Adiguna; Putu Ayu Diah Nareswari (Bali Dermatology and Venereology Journal, 2019)
Background: Psoriasis vulgaris is a chronic inflammatory skin disease that its aetiology is still not completely known. A chronic inflammation in psoriasis can cause organ dysfunctions. Elevation of proinflammatory cytokines gives rise to insulin resistance by inhibiting insulin and glucose transport mechanism signals. Insulin resistance is the underlying pathogenesis of metabolic syndrome.Objective: This study aimed to undestand any correlation in the severity of psoriasis vulgaris with HOMA-IR.Methods: A cross sectional research involving 35 subjects with psoriasis vulgaris and 15 subjects without who met the selection criteria. HOMA-IR is a formula used to measure insulin resistance which calculates the fasting insulin value in Î¼U/ml x fasting glucose in mg/DL/405 taken from the blood veins of subjects. PASI score was used to determine psoriasis vulgaris severity.Results: This study shows that the HOMA-IR median value was higher in psoriasis subject than the subjects without psoriasis (p<0.05). The correlaton analysis shows a moderate positive correlation between psoriasis vulgaris severity and HOMA-IR (r= 0.427; p<0.05). The prevalence ratio was 8.57, which means psoriasis vulgaris subjects were 8.57 times more likely to have HOMA-IR compared to those without psoriasis vulgaris (p<0.05; 95%CI: 1.26-58.1).Conclusion: This study concludes that there is a moderate positive correlation between severity of psoriasis vulgaris and HOMA-IR values.